Catatonia, Neuroleptic Malignant Syndrome, and Cotard Syndrome in a 22-Year-Old Woman: A Case Report - Weiss, C.; Santander, J.; Torres, R. (Case Reports in Psychiatry, 2013)
The following case study describes a 22-year-old woman with depression and symptoms of psychosis who developed neuroleptic malignant syndrome after using Risperidone, thus requiring life support equipment and Bromocriptine, later recovering after seven days. From a psychiatric and neurological point of view, however, the persistence of catatonic syndrome and Cotard syndrome delusions was observed, based on assertions such as “I do not have a heart,” “my heart is not beating,” “I can not breathe,” “I am breaking apart,” “I have no head” (ideas of negation) and statements about the patient being responsible for the “death of the whole world” (ideas of enormity). Brain NMR revealed leukoencephalopathy, interpreted as scar lesions caused by perinatal neurological damage, after discarding other pathologies. The patient responded well to electroconvulsive therapy after 11 sessions. Organic vulnerability to these syndromes, as well as their coexistence and clinical differentiation is discussed in the light of the data observed.